INFLUENCE OF CHARACTERISTICS OF VIRTUAL ANCHOR ON FANS’ REWARD BEHAVIOR: A CASE STUDY OF CHINESE MARKET - Zhou, Chaoran; Lertjanyakit, Hatairat (Academic Journal Phranakhon Rajabhat University, 2024)
This article examined how the characteristics of Virtual Anchors affected fans’ reward behavior during live broadcasts. It also investigated the live broadcast factors influencing the internal states of Virtual Anchor fans and explored whether emotional attachment and identity served as mediating variables. The study was grounded in SOR Theory, supplemented by Body Consumption Theory, Prototype Theory, the "Three Bodies" Theory, Attachment Theory, and Identity Theory, and constructed a reward behavior model for users who have watched Virtual Anchors’ live broadcasts. A quantitative research design was used to collect data and test the hypothetical model. In this survey, 550 questionnaires were distributed, and 507 were successfully recovered. The quantitative data were analyzed using confirmatory factor analysis, path testing, and mediating effect testing. The results showed that the characteristics of Virtual Anchors had a positive impact on fans' reward behavior. The test results confirmed a significant correlation between the independent variables—the external image of the Virtual Anchor ("leather case"), the character setting of the Virtual Anchor, and the personality charm of the Virtual Anchor ("the person in the Virtual Anchor")—the mediating variables of emotional attachment and identity, and the dependent variable of fans’ reward behavior. The Bias-Corrected Bootstrap method confirmed the mediating effect of emotional attachment and identity. This study demonstrated that the characteristics of Virtual Anchors positively influenced fans’ reward behavior.